Fe-based high-entropy alloy with high strength, plasticity, corrosion resistance and soft magnetism as well as preparation method and application of Fe-based high-entropy alloy

Through FeaCobCrcAldMoeCuf formula and high-temperature hot rolling treatment, the contradiction between corrosion resistance, soft magnetic properties and mechanical properties of traditional alloys in extreme marine environments was solved, and a high-strength plastic, corrosion-resistant and soft magnetic Fe-based high-entropy alloy is prepared, suitable for Offshore wind turbines and ship electromagnetic components.

CN119287264APending Publication Date: 2025-01-10DALIAN UNIV OF TECH
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411420103.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional materials are difficult to take into account corrosion resistance, soft magnetic properties and mechanical properties in extreme marine environments. Existing alloys will damage soft magnetic properties when adding corrosion resistance elements, and the strength and soft magnetic properties are inconsistent, making it difficult to design high-strength plastics. , corrosion-resistant, soft magnetic Fe-based high-entropy alloy.

Method used

FeCobCrcAldMoeCuf's high entropy alloy formula is prepared by using FeCobCrcAldMoeCuf's high entropy with excellent soft magnetic properties, good corrosion resistance and high mechanical properties through specific element selection and reasonable molar percentage, combined with vacuum arc smelting and high temperature hot rolling treatment. alloy.

Benefits of technology

A Fe-based high-entropy alloy with excellent corrosion resistance and soft magnetic properties in seawater has a room temperature tensile yield strength of 400~500MPa and a post-break elongation of 20%~30%, and a self-corrosion current density is lower than 316L. Stainless steel, suitable for electromagnetic fields under extreme load conditions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119287264A_ABST
    Figure CN119287264A_ABST
Patent Text Reader

Abstract

The general formula of the high-strength-plasticity, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy is FeaCobCrcAldMoeCuf, a is larger than or equal to 45% and smaller than or equal to 60%, b is larger than or equal to 10% and smaller than or equal to 20%, c is larger than or equal to 20% and smaller than or equal to 30%, d is larger than or equal to 1% and smaller than or equal to 10%, e is larger than or equal to 0% and smaller than or equal to 3%, f is larger than or equal to 0% and smaller than or equal to 4%, a + b + c + d + e + f = 100%, and a, b, c, d, e and f correspond to the molar percentages of elements respectively. The Fe-based high-entropy alloy has excellent soft magnetic performance, meanwhile has good corrosion resistance in seawater and also has certain strong plasticity, the comprehensive performance of the Fe-based high-entropy alloy is superior to that of most traditional alloys, and the alloy has wide application prospects in the electromagnetic field under the extreme load condition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to alloy technology, and in particular to a high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy, and a preparation method and application thereof. Background Art

[0002] As the industrial environment becomes more complex, traditional materials face more challenges. For example, electromagnetic components in underwater submersibles, offshore wind turbines and ships used under certain loads and corrosive environments require not only excellent soft magnetic properties to improve energy conversion efficiency, but also excellent strong plasticity to withstand mechanical loads and excellent corrosion resistance to resist long-term corrosion from seawater. However, the corrosion resistance, soft magnetic properties and mechanical properties of existing materials are contradictory and difficult to balance, which greatly limits the scope of application. For example, 316L stainless steel has excellent corrosion resistance, but poor soft magnetic properties; silicon steel has excellent soft magnetic properties, but poor corrosion resistance, etc. Therefore, it is urgent to design and prepare a soft magnetic material that has both strong plasticity and corrosion resistance to meet the application requirements of soft magnetic materials under extreme marine environmental conditions and certain mechanical loads.

[0003] Usually, if you want to ensure that the alloy has excellent corrosion resistance in seawater, you need to add the corrosion-resistant element chromium, but chromium is an antiferromagnetic element, which will greatly damage the soft magnetic properties of the material. In addition, there is a basic microstructure design conflict between the strength and soft magnetic properties of the alloy. Therefore, how to balance the contradictions between corrosion resistance, soft magnetic properties and mechanical properties, and prepare Fe-based high-entropy alloys with high strength, plasticity, corrosion resistance and soft magnetism is extremely challenging. Summary of the invention

[0004] The purpose of the present invention is to propose a high-strength, plastic, corrosion-resistant, soft-magnetic Fe-based high-entropy alloy to address the conflicting issues among corrosion resistance, soft magnetic properties and mechanical properties in traditional alloys. The alloy has excellent soft magnetic properties, good corrosion resistance in seawater, and certain strength and plasticity. The comprehensive performance of the alloy is better than that of most traditional alloys, and the alloy has broad application prospects in the electromagnetic field under extreme load conditions.

[0005] It should be noted that, in the present invention, unless otherwise specified, the specific meaning of "including" in relation to composition limitations and descriptions includes both open-ended "including", "comprising", etc. and similar meanings, as well as closed-ended "composed of", "composed of", etc. and similar meanings.

[0006] To achieve the above object, the technical solution adopted by the present invention is: a high-strength, plastic, corrosion-resistant, soft-magnetic Fe-based high-entropy alloy, the general formula of which is Fe a Co b Cr c Al d Mo eCu f , where 45%≤a≤60%, 10%≤b≤20%, 20%≤c≤30%, 1%≤d≤10%, 0%≤e≤3% and 0%≤f≤4%, and a+b+c+d+e+f=100%, a, b, c, d, e and f correspond to the molar percentages of the elements respectively.

[0007] Furthermore, the general formula Fe a Co b Cr c Al d Mo e Cu f Among them, 52%≤a≤60%, 12%≤b≤18%, 22%≤c≤26%, 1%≤d≤4%, 1%≤e≤2% and 1%≤f≤2%.

[0008] Furthermore, the self-corrosion current density of the high-strength, high-ductility, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy is 0.13 μA / cm 2 , better than 316L stainless steel, the saturation magnetization (Ms) is 140-155emu / g, the coercive force (Hc) is 1.5-2.0Oe, the room temperature tensile yield strength is 400-500MPa, the tensile strength is 500-585MPa, and the elongation after break is 20%-30%.

[0009] Another object of the present invention is to disclose a method for preparing a high-strength, high-ductility, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy, comprising the following steps:

[0010] Firstly, the surfaces of metal single substance raw materials Fe, Co, Cr, Al, Mo and Cu are polished and ultrasonically cleaned, and the raw materials are fully dried after cleaning; then the raw materials are weighed according to the general formula; the weighed raw materials Fe, Co, Cr, Al, Mo and Cu are placed in a vacuum arc melting furnace, and melted under argon protection to obtain high entropy alloy button ingots; the high entropy alloy button ingots are hot rolled, and after hot rolling, the alloy is placed in a heat treatment furnace for high temperature annealing treatment, so as to obtain a Fe-based high entropy alloy with high strength, plasticity, corrosion resistance and soft magnetism.

[0011] Furthermore, the raw materials Fe, Co, Cr, Al, Mo and Cu are all industrial-grade pure raw materials with a purity of 99.9wt.% or more.

[0012] Furthermore, when melting the alloy, Al with a low melting point is placed at the bottom of the crucible, and the remaining Fe, Co, Cr, Mo and Cu are covered on Al.

[0013] Furthermore, before smelting, the vacuum degree of the arc furnace was pumped to 3×10 -3 ~4×10 -3Pa, and then fill with argon to -0.05 ~ -0.04MPa, and before smelting, the Ti ingot needs to be smelted 2 to 4 times, each time for 60 to 80s, to remove excess oxygen as much as possible.

[0014] Furthermore, the smelting current is 300-500A, the ingot is repeatedly turned over and smelted 5-7 times, and each smelting time is 120-150s.

[0015] Furthermore, the alloy is air-cooled after hot rolling, and then water-quenched after high-temperature annealing.

[0016] Furthermore, the hot rolling temperature is 1000-1200° C., and the hot rolling deformation is 70%-90%.

[0017] Furthermore, the heat treatment temperature of the high temperature annealing treatment is 1100-1200° C., the time is 10-60 min, and then a water quenching treatment is performed.

[0018] Another object of the present invention is to disclose the use of the high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy in the electromagnetic field.

[0019] Furthermore, the high-strength, plastic, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy is particularly suitable for metal parts of ships and offshore wind turbines operating under certain loads and corrosive environments.

[0020] The formula of the high-strength, high-plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of the present invention is scientific and reasonable, and the preparation method thereof is simple and easy to implement. Compared with the prior art, it has the following advantages:

[0021] 1) The high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of the present invention comprises specific element selection and reasonable ratio, wherein Fe and Co are used to improve the magnetic properties of the alloy, Cr and Mo elements improve the corrosion resistance of the alloy, Cu element improves the corrosion resistance and antibacterial properties of the alloy, and Al element improves the corrosion resistance and mechanical properties of the alloy while forming a BCC structure of the material.

[0022] 2) The high-strength, plastic, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy of the present invention exhibits good mechanical properties after high-temperature hot rolling and heat treatment, with a room temperature tensile yield strength of 400 to 500 MPa, a tensile strength of 500 to 585 MPa, and an elongation after fracture of 20% to 30%.

[0023] 3) The high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of the present invention has excellent soft magnetic properties, with a saturation magnetization (Ms) of 140 to 155 emu / g and a coercive force (Hc) of 1.5 to 2.0 Oe.

[0024] 4) The high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of the present invention has excellent corrosion resistance, excellent corrosion resistance in 3.5wt.% NaCl (simulated seawater) solution, and the self-corrosion current density (0.13-0.14μA / cm 2 ) is less than that of 316L stainless steel (0.29μA / cm2), its pitting potential (997~1113mV) is much greater than that of 316L stainless steel (367mV), and the stability of the passivation film is far superior to that of 316L stainless steel.

[0025] 5) The raw materials of the high-strength, high-plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of the present invention are easy to obtain, the preparation process is simple and easy, and the excellent soft magnetic properties, mechanical properties and corrosion resistance are combined, so that the alloy has a wide range of application prospects in the electromagnetic field under extreme load conditions. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] Figure 1 (a) is the hysteresis loop of the high-strength, plastic, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy of Example 1 at room temperature, and (b) is an enlarged view of the central part of the hysteresis loop;

[0027] Figure 2 The potentiodynamic polarization curves of the electrochemical corrosion test of the high-strength, plastic, corrosion-resistant, soft-magnetic Fe-based high-entropy alloy and 316L stainless steel in 3.5wt.% NaCl solution of Example 1 are shown;

[0028] Figure 3 The room temperature tensile engineering stress-strain curve of the high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of Example 1;

[0029] Figure 4 The XRD diffraction analysis spectrum of the high-strength, high-plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of Example 1;

[0030] Figure 5 This is the SEM microstructure diagram of the high-strength, high-ductility, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy of Example 1;

[0031] Figure 6 (a) is the hysteresis loop of the high-strength, plastic, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy of Example 2 at room temperature, and (b) is an enlarged view of the central part of the hysteresis loop;

[0032] Figure 7 The potentiodynamic polarization curves of the electrochemical corrosion test of the high-strength, plastic, corrosion-resistant, soft-magnetic Fe-based high-entropy alloy and 316L stainless steel in 3.5wt.% NaCl solution of Example 2 are shown;

[0033] Figure 8The room temperature tensile engineering stress-strain curve of the high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of Example 2;

[0034] Fig. 9 This is the XRD diffraction analysis spectrum of the high-strength, plastic, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy of Example 2. DETAILED DESCRIPTION

[0035] The present invention is further described below with reference to the examples. The description of the technical features described below is based on representative embodiments and specific examples of the present invention, but the present invention is not limited to these embodiments and specific examples. It should be noted that:

[0036] Unless otherwise stated, the units used in this specification are all international standard units, and the numerical values ​​and numerical ranges appearing in the present invention should be understood to include the inevitable systematic errors in industrial production.

[0037] In this specification, the numerical range expressed using "a numerical value A to a numerical value B" means a range including the endpoints numerical values ​​A and B.

[0038] In the present specification, a numerical range expressed using "above" or "below" means a numerical range including the number.

[0039] In this specification, the word "may" means both performing a certain process and not performing a certain process.

[0040] In this specification, the use of "optional" or "optional" indicates that certain substances, components, execution steps, application conditions and other factors are used or not used.

[0041] In this specification, when "normal temperature" or "room temperature" is used, the temperature may be 15-25°C.

[0042] In this manual, the reagents or instruments used without indicating the manufacturer are all conventional products that can be obtained through commercial purchase.

[0043] Example 1

[0044] This embodiment discloses a high-strength, high-ductility, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy, the general formula of which is Fe 58 Co 15 Cr 25 Al 2 , the specific preparation method is as follows:

[0045] Industrial grade pure raw materials Fe, Co, Cr and Al with a purity of more than 99.9wt.% are weighed according to the molar ratio of each component in the general formula. The prepared raw materials are placed in a vacuum arc melting furnace, and the low melting point Al metal single substance is placed at the bottom of the crucible. The remaining Fe, Co and Cr metal single substances are covered on Al to prevent the low melting point elements from volatilizing. The vacuum degree is drawn to 3×10 -3 Pa, then high-purity argon is filled to make the vacuum degree reach -0.05MPa. Before smelting, the Ti ingot is smelted 2 to 3 times, each time for 60 to 80 seconds, to remove the remaining oxygen in the furnace, and then the soft magnetic high entropy alloy is smelted. During the smelting process, the current is controlled at 300 to 500A, and the smelting is repeated 6 times. Each smelting arc lasts for 2 to 3 minutes to obtain a soft magnetic high entropy alloy ingot. The soft magnetic high entropy alloy ingot is hot rolled at a rolling temperature of 1100°C and a rolling deformation of 85%. The hot-rolled alloy is subjected to high-temperature solution treatment at a heat treatment temperature of 1150°C for 20 minutes and water quenching to prepare a Fe-based high entropy alloy with high strength, plasticity, corrosion resistance and soft magnetic properties.

[0046] Figure 1 The Fe prepared in Example 1 58 Co 15 Cr 25 Al 2 The hysteresis loop and the local enlarged image of the central area of ​​the high-entropy alloy show that its saturation magnetization (Ms) is 152emu / g and its coercive force (Hc) is 1.95Oe, which shows excellent soft magnetic properties. Figure 2 The Fe prepared in Example 1 58 Co 15 Cr 25 Al 2 Potentiodynamic polarization curves of electrochemical corrosion test of high entropy alloy and 316L stainless steel in 3.5wt.%NaCl solution. The self-corrosion current density of high entropy alloy in this example (0.14μA / cm 2 ) is less than 316L stainless steel (0.29μA / cm 2 ), its pitting potential (997mV) is much greater than that of 316L stainless steel (367mV), indicating that the alloy of this embodiment has excellent corrosion resistance and its corrosion resistance exceeds that of 316L stainless steel; Figure 3 The Fe prepared in Example 1 58 Co 15 Cr 25 Al 2 The tensile engineering stress-strain curve of the high entropy alloy shows that the tensile strength, yield strength and fracture plasticity are 513MPa, 418MPa and 30% respectively, showing relatively excellent mechanical properties. Figure 4 and Figure 5 are respectively Fe prepared in Example 1 58 Co15 Cr 25 Al 2 XRD spectrum and SEM microstructure of the high entropy alloy show that the alloy exhibits a single BCC structure.

[0047] Example 2

[0048] This embodiment discloses a high-strength, high-ductility, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy, the general formula of which is Fe 56 Co 14 Cr 24 Al 3 Mo 1 Cu 2 , and its preparation method is as follows:

[0049] Industrial grade pure raw materials Fe, Co, Cr, Al, Mo and Cu with a purity of more than 99.9wt.% are weighed according to the molar ratio of each component in the general formula. The prepared raw materials are placed in a vacuum arc melting furnace, and the low melting point Al metal single substance is placed at the bottom of the crucible. The remaining Fe, Co, Cr, Al, Mo and Cu metal single substances are covered on Al to prevent the low melting point elements from volatilizing. The vacuum degree is drawn to 3×10 -3 Pa, then high-purity argon is filled to make the vacuum degree reach -0.05MPa. Before smelting, the Ti ingot is smelted 2 to 3 times, each time for 60 to 80 seconds, to remove the remaining oxygen in the furnace, and then the soft magnetic high entropy alloy is smelted. During the smelting process, the current is controlled at 300 to 500A, and the smelting is repeated 6 times. Each smelting arc lasts for 2 to 3 minutes to obtain a soft magnetic high entropy alloy ingot. The soft magnetic high entropy alloy ingot is hot rolled at a rolling temperature of 1100°C and a rolling deformation of 85%. The hot-rolled alloy is subjected to high-temperature solution treatment at a heat treatment temperature of 1150°C for 20 minutes and water quenching to prepare a Fe-based high entropy alloy with high strength, plasticity, corrosion resistance and soft magnetic properties.

[0050] Figure 6 The Fe prepared in Example 2 56 Co 14 Cr 24 Al 3 Mo 1 Cu 2 The hysteresis loop and the local enlarged image of the central area of ​​the high entropy alloy show that its saturation magnetization (Ms) is 144emu / g and the coercive force (Hc) is 1.9Oe, indicating that the alloy has excellent soft magnetic properties. Figure 7 The Fe prepared in Example 2 56 Co 14 Cr 24 Al 3 Mo 1 Cu 2Potentiodynamic polarization curves of electrochemical corrosion test of high entropy alloy and 316L stainless steel in 3.5wt.%NaCl solution. The self-corrosion current density of high entropy alloy in this example (0.13μA / cm 2 ) is less than 316L stainless steel (0.29μA / cm 2 ), its pitting potential (1113mV) is much greater than that of 316L stainless steel (367mV), indicating that the alloy of this embodiment has good corrosion resistance and its corrosion resistance exceeds that of 316L stainless steel; Figure 8 The Fe prepared in Example 2 56 Co 14 Cr 24 Al 3 Mo 1 Cu 2 The tensile engineering stress-strain curve of the high entropy alloy shows that the tensile strength, yield strength and fracture plasticity are 585MPa, 505MPa and 24% respectively, showing relatively excellent mechanical properties. Fig. 9 The Fe prepared in Example 2 56 Co 14 Cr 24 Al 3 Mo 1 Cu 2 XRD pattern of high entropy alloy. The results show that the alloy is composed of a single BCC structure.

[0051] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. A high-strength, high-plastic, corrosion-resistant, soft-magnetic Fe-based high-entropy alloy, characterized in that: Its general formula is Fe a Co b Cr c Al d Mo e Cu f , where 45%≤a≤60%, 10%≤b≤20%, 20%≤c≤30%, 1%≤d≤10%, 0%≤e≤3% and 0%≤f≤4%, and a+b+c+d+e+f=100%, a, b, c, d, e and f correspond to the molar percentages of the elements respectively.

2. A method for preparing the high-strength, high-ductility, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy according to claim 1, characterized in that: The following steps are involved: Firstly, the surfaces of metal single substance raw materials Fe, Co, Cr, Al, Mo and Cu are polished and ultrasonically cleaned, and the raw materials are fully dried after cleaning; then the raw materials are weighed according to the general formula; the weighed raw materials Fe, Co, Cr, Al, Mo and Cu are placed in a vacuum arc melting furnace, and melted under argon protection to obtain high entropy alloy button ingots; the high entropy alloy button ingots are hot rolled, and after hot rolling, the alloy is placed in a heat treatment furnace for high temperature annealing treatment, so as to obtain a Fe-based high entropy alloy with high strength, plasticity, corrosion resistance and soft magnetism.

3. The method for preparing the high-strength, high-ductility, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy according to claim 2, characterized in that: The raw materials Fe, Co, Cr, Al, Mo and Cu are all industrial grade pure raw materials with a purity of more than 99.9 wt.%.

4. According to the method for preparing the high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of claim 2, when smelting the alloy, Al with a low melting point is placed at the bottom of the crucible, and the remaining Fe, Co, Cr, Mo and Cu are covered on Al.

5. According to the method for preparing the high-strength, high-ductility, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of claim 2, before smelting, the vacuum degree of the arc furnace is pumped to 3×10 -3 ~4×10 -3 Pa, and then fill with argon to -0.05 ~ -0.04MPa, and before smelting, the Ti ingot needs to be melted 2 to 4 times, each time for 60 to 80s.

6. According to the preparation method of the high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of claim 2, the smelting current is 300-500A, the ingot is repeatedly turned over and smelted 5-7 times, and the smelting time each time is 120-150s.

7. According to the method for preparing the high-strength, ductile, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of claim 2, the alloy is air-cooled after hot rolling, and then the alloy is water-quenched after high-temperature annealing.

8. According to the method for preparing the high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of claim 2, the hot rolling temperature is 1000-1200°C, and the hot rolling deformation is 70%-90%.

9. According to the method for preparing the high-strength, plastic, corrosion-resistant and soft-magnetic Fe-based high-entropy alloy of claim 2, the heat treatment temperature of the high-temperature annealing treatment is 1100-1200°C, the time is 10-60 minutes, and then a water quenching treatment is performed.

10. Use of the high-strength, plastic, corrosion-resistant, and soft-magnetic Fe-based high-entropy alloy according to claim 1 in the electromagnetic field.